2012
DOI: 10.1111/j.1467-6494.2011.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐Factor Personality Traits and Age Trajectories of Self‐Rated Health: The Role of Question Framing

Abstract: We examined the influence of personality traits on mean levels and age trends in four single-item measures of self-rated health: General rating, comparison to age peers, comparison to past health, and expectations for future health. Community-dwelling participants (N = 1,683) completed 7,474 self-rated health assessments over a period of up to 19-years. In hierarchical linear modeling analyses, age-associated declines differed across the four health items. Across age groups, high neuroticism and low conscienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
81
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 79 publications
13
81
1
6
Order By: Relevance
“…Neuroticism, besides being a risk factor to trigger depression, represents a risk for functional decline among the elderly in the future (Tsubota-Utsugi et al, 2014) and it is associated to Alzheimer's Disease (Terracciano et al, 2014). Some studies state the hypothesis that Neuroticism is related to reduced brain volume (Knutson, Momenan, Rawlings, Fong, & Hommer, 2001) and to risk behaviors to health such as metabolic syndrome, early mortality (Löckenhoff et al, 2012), and inflammation (Sutin et al, 2010). Additionally, individuals with high Neuroticism levels tend to evaluate their health pessimistically and present unfavorable social comparisons (Löckenhoff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroticism, besides being a risk factor to trigger depression, represents a risk for functional decline among the elderly in the future (Tsubota-Utsugi et al, 2014) and it is associated to Alzheimer's Disease (Terracciano et al, 2014). Some studies state the hypothesis that Neuroticism is related to reduced brain volume (Knutson, Momenan, Rawlings, Fong, & Hommer, 2001) and to risk behaviors to health such as metabolic syndrome, early mortality (Löckenhoff et al, 2012), and inflammation (Sutin et al, 2010). Additionally, individuals with high Neuroticism levels tend to evaluate their health pessimistically and present unfavorable social comparisons (Löckenhoff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies state the hypothesis that Neuroticism is related to reduced brain volume (Knutson, Momenan, Rawlings, Fong, & Hommer, 2001) and to risk behaviors to health such as metabolic syndrome, early mortality (Löckenhoff et al, 2012), and inflammation (Sutin et al, 2010). Additionally, individuals with high Neuroticism levels tend to evaluate their health pessimistically and present unfavorable social comparisons (Löckenhoff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that high Conscientiousness and Extraversion, and low Neuroticism were linked to better comparative expectations for future health in the bivariate analyses, and in the path analysis through preventive health behaviors, only Conscientiousness and Agreeableness were significant predictors. Results from a large lifespan study demonstrated that Conscientiousness, Agreeableness and Neuroticism were not associated with FSRH prospectively, whereas Extraversion and Openness were [7]. Neuroticism was, however, a significant predictor of declines in FSRH over time.…”
Section: Personality and Future Healthmentioning
confidence: 99%
“…This model posits that the evaluation of subjective health is a necessarily contextualized multi-stage process that goes beyond the initial assessment of current objective health indicators that may influence future health (e.g., symptoms, behavior, and genetics). Accordingly, SRH is heavily influenced by other contextual factors such as personality and expectations which can contour the appraisals of these objective indicators [1,7,8]. Indeed, certain personality factors associated with negative affect, such as Neuroticism, are known to influence the perception and evaluation of symptoms [9].…”
Section: Personality and Future Healthmentioning
confidence: 99%